Transformational leadership and teacher resilience in Chinese Universities: The chain mediating role of perceived organisational support and work engagement - Ziliang Li; Liqin Liu; Yan Lin (PLoS ONE, 2026)
In the context of global changes in higher education, the development mechanism of teachers’ professional resilience, as a key psychological capital for maintaining education quality and institutional core competitiveness, needs to be systematically examined. Based on the organisational context of Chinese higher education institutions, this study integrates the social exchange theory and the job requirement-resource model to construct a chain-mediated theoretical framework of transformational leaders’ influence on teachers’ professional resilience through the sense of organisational support and work engagement. Based on 712 college teachers’ multi-temporal tracking data, a bias-corrected Bootstrap structural equation modelling test found that transformational leadership had a significant positive drive on teachers’ professional resilience (total effect β = 0.72, 95% CI=[0.63, 0.81]), of which 44.4% originated from the direct effect (β = 0.32), and 36.1% was independently transmitted through the work-input mediated path (β = 0.26, 95%CI=[0.19, 0.33]), and 19.4% mediated by the chain of “transformational leadership → sense of organisational support (β=0.62) → work engagement (β=0.41) → professional resilience (β=0.55)” (effect size β = 0.14, 95%CI=[0.10, 0.20]). This study empirically reveals the sequential transmission mechanism of “leadership behaviour - perceived organisational support - work engagement - psychological resilience generation”, to clarify the internal mechanism of the stepwise transformation from emotional support to behavioural activation, and to provide a theoretical paradigm and a practical path for colleges and universities to enhance teachers’ resilience through leadership development and organisational support system reconfiguration.